Cybersecurity engineering a secure information technology organization /c Dan Shoemaker, Kenneth Sigler - Shoemaker, Dan; Sigler, Kenneth (Cengage Learning, 2015)
Provides a guide to software security, ranging far beyond secure coding to outline rigorous processes and practices for managing system and software lifecycle operations. This book opens with a guide to the software lifecycle, covering all elements, activities, and practices encompassed by the universally accepted ISO/IEEE 12207-2008 standard